POSSIBLE DEGRADATION MECHANISM IN ZNS-MN ALTERNATING-CURRENT THIN-FILM ELECTROLUMINESCENT DISPLAY - LEE, YH; CHUNG, IJ; OH, MH (AMER INST PHYSICS, 1991)
To study origins of alternating current thin-film electroluminescent display (AC-TFELD) degradation phenomena, we have fabricated two different types of AC-TFELD with multilayered insulators. For an accelerated aging, high-frequency voltages were applied and brightness versus operating time characteristics were measured. Surface morphology (SEM), Auger electron spectroscopy (AES) in-depth profiles, and AES spectra were examined for the aged devices with and without Si3N4 interlayers. From the obtained results, we proposed that the formation of zinc-oxy-sulfides in ZnS:Mn-insulator at the ITO side may play a significant role in the aging phenomena and degradation of brightness (B)-operating time (T) characteristics for our devices. Therefore, we suggest that the dielectric interlayer of stable stoichiometry must be inserted in ZnS:Mn-insulator at the In2O3-SnO2(ITO) side to improve the aging characteristics.
Keywords: DEVICES